The aristocratic families of early imperial China a case study of the Po-ling Tsʻui family - Ebrey, Patricia Buckley 1947- (Cambridge studies in Chinese history, literature, and institutions, 1978)
Much scholarly work has been published on the Chinese medieval 'aristocracy', in Chinese, Japanese and Western languages. It is commonly accepted that the change from an aristocratic society to a 'meritocracy' was one of the turning points of Chinese history. But since almost every aspect of political, economic and cultural history is involved in questions of the nature of the aristocracy, perhaps the only way to test theories of the means by which a small elite preserved its social status and political prestige for seven or eight hundred years is by tracing the fortunes of a single family in great detail. The present work is a fully documented case study of the Ts'uis of Po-ling from the first through the ninth centuries. By observing OW evolution of the Ts'uis as an aristocratic kinship group – and an unusual quantity of rich and original source material was available to Dr Ebrey – the author demonstrates OW fluctuation in aristocratic influence and tic changing basis of such families' prestige and power. Studies such as this are essential to enlarge our knowledge not only of medieval society and politics in China but also the development of family and lineage. In the light of the detailed evidence Dr Ebrey provides, many conventional views many well have to be abandoned